Effect of Educational Videos on Knowledge, Attitudes, and Practices of Ear Health: A Quasi-Experimental Study among Medical Students in Yogyakarta, Indonesia - Arsyada Hakama Syakuro; Asti Widuri; Rizka Fakhriani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Many hearing problems arise from a lack of understanding about ear health and proper care. Lack of public awareness of how to maintain ear health, coupled with improper ear cleaning techniques such as using cotton swabs or other instruments, can lead to earwax blockages or infections in the outer ear. Some ear infections can be prevented by public health promotion activities, including videos. This study aims to examine the effect of ear health education videos on knowledge, attitudes, and ear cleaning practices. Methods: This study used a quasi-experimental pre-test and post-test design. Sixty-three medical students were recruited using consecutive sampling. After obtaining informed consent, they were asked to complete a valid and reliable Indonesian version questionnaire on knowledge, attitudes, and practices (KAP) of ear health, watch an educational video about anatomy, physiology, and ear health safety care, and then complete the same questionnaire again. Results: The research respondents were 38 (60.3%) female students and 25 (39.7%) male students. Overall KAP scores improved significantly after video intervention (Z = -3.92, p < 0.001, r = 0.49, 95% CI = [0.28-0.66]). Stratified analysis of each domain revealed heterogeneous outcomes. Knowledge and attitude scores showed a non-significant increase, but practices improved significantly with a small to moderate effect (Z = -2.03, p = 0.042, r = 0.26, 95% CI = [0.40-3.00]), particularly regarding avoidance of unsafe ear cleaning tools and noise exposure. Conclusion:Ear health video education did not substantially alter knowledge and attitude, but it produced significant behavioral shifts in self-reported ear-care practices. The absence of substantial change in knowledge and attitude ratings may be due to a high baseline level in this cohort, indicating a possible ceiling effect. This behavioral shift aligns with theories suggesting that multimedia interventions effectively improve procedural skills and self-efficacy, aiding the application of existing knowledge into positive action rather than promoting deeper conceptual change.